2016
DOI: 10.1007/s13594-016-0294-1
|View full text |Cite
|
Sign up to set email alerts
|

Bovine milk antioxidant properties: effect of in vitro digestion and identification of antioxidant compounds

Abstract: Milk proteins contained encrypted in their sequence biologically active components that can be released by enzymatic hydrolysis. Among the biological activities recognized in milk components, the antioxidant activity is of great interest.\ud The objective of the present study was to analyse the antioxidant properties of whole, semi-skimmed and skimmed milk during simulated gastrointestinal digestion and to identify the compounds responsible for the antioxidant activity. Simulated digestion\ud increased the 2,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 31 publications
2
31
0
1
Order By: Relevance
“…In fact, free radicals are deactivated by peptides containing hydrophobic and aromatic amino acids (such as Y, H, P, W) and selected free amino acids (Y and C) [101,117]. In particular, the presence of Y and W residues in the peptides sequences is considered essential for a significant increase of the antioxidant effect, because of its strong ability to donate a proton [65,118,119]. Actually, their occurrence into the sequences of dipeptides is usually recognized as responsible for antioxidant activities [120].…”
Section: Antioxidant Peptides Identified In Commercial Fermented Dairmentioning
confidence: 99%
“…In fact, free radicals are deactivated by peptides containing hydrophobic and aromatic amino acids (such as Y, H, P, W) and selected free amino acids (Y and C) [101,117]. In particular, the presence of Y and W residues in the peptides sequences is considered essential for a significant increase of the antioxidant effect, because of its strong ability to donate a proton [65,118,119]. Actually, their occurrence into the sequences of dipeptides is usually recognized as responsible for antioxidant activities [120].…”
Section: Antioxidant Peptides Identified In Commercial Fermented Dairmentioning
confidence: 99%
“…The ABTS assay was carried out as described above. The capacity to scavenge hydroxyl radicals was evaluated according to Tagliazucchi, Helal, Verzelloni, & Conte (2016c). In the assay, 50 μL of appropriately diluted samples or standard (vitamin C) were mixed with 50 μL of TPTZ (2,4,6-tri(2pyridyl)-S-triazine) at a concentration of 3 mmol L −1 , 50 μL of 3 mmol L −1 FeSO4, and 50 μL of 0.01% (v/v) hydrogen peroxide, in a clear bottom 96-well plate.…”
Section: Antioxidant Activities Analysismentioning
confidence: 99%
“…It should be noted that many peptides in the treated yogurt contained hydrophobic amino acid residues, such as valine, leucine, proline, cysteine, histidine and methionine (Table ). It has been confirmed that tyrosine and cysteine residues can contribute the radical scavenging property to peptides, whereas proline, valine, leucine, phenylalanine and histidine in peptides play roles in inhibiting lipid peroxidation (Tagliazucchi et al ., ). Different from the microbial transglutaminase‐treated yogurt, the β‐casein‐derived peptides, including PYPQ, VLPVPQKAVPYPQ and PVPQKAVPYPQ, were considered the antioxidative peptides in the control yogurt (Table ), as their domain PYPQ has been confirmed to participate in antioxidant activity (Rival et al .,).…”
Section: Resultsmentioning
confidence: 97%
“…Different from the microbial transglutaminase‐treated yogurt, the β‐casein‐derived peptides, including PYPQ, VLPVPQKAVPYPQ and PVPQKAVPYPQ, were considered the antioxidative peptides in the control yogurt (Table ), as their domain PYPQ has been confirmed to participate in antioxidant activity (Rival et al .,). Additionally, the κ‐casein‐derived peptide VLSRYPSYGLN and PIQYVLSRYPSY were also considered to have antioxidant properties as the sequence YPS was reported to provide antioxidative feature to the peptide AYPS, SRYPS, and RYPS (De Gobba et al ., ; Tagliazucchi et al ., ). Moreover, a long peptide QPTTMARHPHPHLSFMAI (κ‐casein 82‐99) found in the control yogurt might be the precursor of an antioxidant peptide HPHPHLSF (Gómez‐Ruiz et al ., ).…”
Section: Resultsmentioning
confidence: 97%